Soil organic carbon accumulation under perennial forages in the Southern Highlands of Tanzania - Nyawira, Sylvia S.; Birthe, Paul; Korir, M.J.; Nzogela, B.; Notenbaert, An Maria Omer (2021)
Joint International Grassland & International Rangeland Kenya 2021 Virtual Congress